Chemokine CXCL8 promotes HIV-1 replication in human monocyte-derived macrophages and primary microglia via nuclear factor-κB pathway. - Manmeet K Mamik; Anuja Ghorpade (PLoS ONE, 2014)
Chemokine CXCL8 is an important neutrophil chemoattractant implicated in various neurodegenerative disorders. Cytokine/chemokine imbalance, with an increase in proinflammatory cytokines like interleukin-1β and tumor necrosis factor-α within the central nervous system, is a hallmark of human immunodeficiency virus (HIV)-1 infection. We previously reported that HIV-1 infection is linked to upregulation of CXCL8 in brain tissues and human astrocytes. Chemokines play crucial roles in trafficking of leukocytes and trafficking of HIV-1-infected across the blood-brain barrier play an important role in HIV-1 central nervous system disease. In the post-antiretroviral therapy era, low level of productive replication of HIV-1 in brain is a critical component of neuropathogenesis regulation. The present study investigated the effect of CXCL8 on productive infection of HIV-1 in human monocytes-derived macrophages (MDM) and primary human microglia.Human MDM and microglia were infected with the blood or brain derived HIV-1 isolates, HIV-1ADA or HIV-1JRFL. Treatment with CXCL8 significantly upregulated HIV-1p24 levels in supernatants of both HIV-1-infected MDM as well as microglia. In addition, the formation of 2-long terminal repeat (LTR) circles, a measure of viral genome integration, was significantly higher in CXCL8-treated, HIV-1-infected MDM and microglia. Transient transfection of U937 cells with HIV-1 LTR luciferase reporter construct resulted in increased promoter activity when treated with CXCL8. Moreover, increased nuclear translocation of nuclear factor-κB was seen in HIV-1-infected MDM following CXCL8 treatment. Blocking CXCL8 receptors CXCR1 and CXCR2 abrogated the CXCL8-mediated enhanced HIV-1 replication.Our results show that CXCL8 mediates productive infection of HIV-1 in MDM and microglia via receptors CXCR1 and CXCR2. These results demonstrate that CXCL8 exerts its downstream effects by increasing translocation of nuclear factor-κB into the nucleus, thereby promoting HIV-1 LTR activity.